Emerging trends in superhydrophobic surface based magnetic materials: fabrications and their potential applications. Issue 7 (21st February 2015) - Nagappan, Saravanan; Ha, Chang-Sik
<x xml:space="preserve">Abstract</x> This review covers the fabrications of superhydrophobic surface based magnetic materials (SSBMMs) and their applications.